Seeing things by Anna Margolin = Widzenia rzeczy Anny Margonin - Francuz, Aleksandra (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
If we recall the most important words for the poetry, we should begin the story with the stones, lily, hands and blood, which, if you look at them with the philological accuracy, are interrelated: situate themselves clearly on opposite banks of the creative process.
Keywords: feminine Yiddish poetry of the twentieth century; neoclassicism; acmeism; Dinggedicht; Margolin, Anna (właśc. Lebensboim, Rosa Harning; 1887-1952); kobieca poezja jidysz XX wieku; neoklasycyzm; akmeizm